Growth speed of single edge pre-crack in graphene sheet under tension. (September 2017) - Hua, Jun; Liu, Qinlong; Hou, Yan; Wu, Xiaxia; Zhang, Yuhui
Highlights: The crack speed depends on both the initial crack length and the strain loading rate. The effect of strain loading rate is mainly activated during the crack propagation. The stress intensity factor is 3.2 MPa m and the limit of crack speed is 8400 m/s according to Motto's theory. Abstract: Molecular dynamics simulation is used to study the crack propagation in pre-cracked single layer armchair graphene under tension with constant strain rate. It is found that the surface free energy of graphene is 5.1 J/m 2 and the stress intensity factor is 3.2 MPa m . But the crack speed is not a constant during the crack growing process. The limit of crack speed is 8400 m/s. The crack speed depends on both the initial crack length and the strain loading rate. The shorter the initial crack length, the faster the crack speed. Higher strain loading rate can improve the crack speed, but the maximum speed can't exceed the limit speed. With the increase of initial crack length, the influence of initial crack length decreases and the strain loading rate effect increases. Furthermore, it is found that the effect of strain loading rate is mainly activated during the crack propagation.